Epidemiological data on HIV-infected patients and the importance of education regarding the infection rate. An analytical cross-sectional study - Costa, Víctor de Oliveira; Bresse, Matheus; Costa, Bruna Malaquias Arguelles da; Machado, Nathália Munck; Moura, Marcos de Assis (São Paulo Medical Journal, 2022)
BACKGROUND: Sexually transmitted diseases (STIs) are an important public health problem in all countries. Knowledge of their relationship with the various socioeconomic levels is necessary for an understanding of their epidemiology and behavior in society. OBJECTIVE: To investigate the epidemiology of human immunodeficiency virus (HIV)-positive patients and to correlate education with history of sexually transmitted diseases, especially for syphilis. DESIGN AND SETTING: Analytical cross-sectional study carried out in the city of Juiz de Fora, Minas Gerais, Brazil. METHODS: The medical records of HIV/acquired immunodeficiency syndrome (AIDS) patients who started antiretroviral therapy (ART) between January 2010 and July 2018 were assessed. These patients were attended at the specialized assistance service for HIV/AIDS) of the Department of Sexually Transmitted Diseases (STD/AIDS) of the city of Juiz de Fora. In total, 335 patients were selected. RESULTS: In our sample, 73.13% were male; 57.36% were aged between 25 and 45 years and 24.23% were over 45 years of age. Regarding sexual orientation, 61.78% were homosexual. Regarding education, 52.88%had “unskilled education”, while 47.12% had “qualified education”. Analysis on the relations hip between schooling and syphilis, a positive relationship between qualified schooling and syphilis was observed: odds ratio = 3.588; 95% confidence interval: 1.090-11.808. CONCLUSION: Homosexual male patients are most affected by HIV. Furthermore, this disease is not limited only to individuals with low education. Syphilis should be suspected in all individuals.